2005
DOI: 10.1007/s00268-004-7615-x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Meckel’s Diverticulum in Appendicitis — A Retrospective Analysis of 233 Cases

Abstract: Conflicting reports are found in the literature concerning whether to remove an incidentally discovered Meckel's diverticulum (MD). Between 1.1.1974 and 31.12.2000, at a single center, the perioperative data associated with appendectomy (AE) were recorded consecutively and analyzed retrospectively. All patients in whom an MD was discovered during an AE were included in the study. The clinical presentation, postoperative course, and follow-up in all MDs left in place were analyzed. During the course of 7927 AE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 31 publications
2
45
0
6
Order By: Relevance
“…In one study, 11% of children with complicated MDs were initially diagnosed with appendicitis 6 . Ueberrueck et al found that 5 MDs were found incidentally in a series of 311 appendicectomies performed at one institution over 3 year 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In one study, 11% of children with complicated MDs were initially diagnosed with appendicitis 6 . Ueberrueck et al found that 5 MDs were found incidentally in a series of 311 appendicectomies performed at one institution over 3 year 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in elective diverticulectomy is close to zero and mortality in complicated cases is 1% -10% [6,8]. The generally accepted approach is neither to search for a diverticulum nor to excise the diverticulum if it contains ectopic mucosa or the appendix shows lowgrade inflammation and to leave it in place in case of a perforated or gangrenous appendicitis presence but the experience and preference of the operating surgeon are an important factor [2]. The two cases presented in this study are relevant to this discussion.…”
Section: Discussionmentioning
confidence: 99%
“…The most important factors in making this decision are whether the appendix is perforated or inflamed and the macroscopic appearance of the Meckel's diverticulum [2]. Appendectomy is the main reason for laparotomy application in children and the incidence of intestinal obstruction occurring in the early period after appendectomy is 1.3% -8.3% with higher rates in complicated appendicitis [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study concluded in establishing the importance of exploring the bowel in all appendectomy cases. [13] In patients with the preoperative workup that raises suspicion for, but without an intraoperative verification of, an acute appendicitis, an exploration of 180 cm of the small bowel from the ileocecal valve is advocated. Both pathologies being present, is very rare, and therefore little is to be gained by searching for a diverticulum where acute appendicitis is present and dealt with.…”
Section: Discussionmentioning
confidence: 99%